Characterization and Therapeutic Assessment of Phytomediated Silver Nanoparticles Produced from the Stem Bark of Bombax ceiba - Dharavath, Narendhar; Porika, Mahendar; Tippani, Radhika; Kola, Anand Kishore; Murigingayil Joseph, Tomy; Shevtsov, Maxim; Sonawane, Shirish H (Drug Research, 2025)
The study aims to develop an environmentally friendly method of producing silver nanoparticles using an extract from Bombax ceiba stem bark (Bc-AgNPs) and to investigate their potential medical applications, such as preventing blood cell damage, combating oxidation, and lowering inflammation. The synthesized Bc-AgNPs were characterized using UV–visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy, and transmission electron microscopy (TEM). The zeta potential examination revealed a highly stable colloidal solution of Bc-AgNPs with a surface charge of−14 mV. The synthesized Bc-AgNPs had a face-centred cubic structure with a crystalline size of 26 nm and an average grain size of 59.8 nm, as seen in the TEM images. Bc-AgNPs showed no hemolysis at varied concentrations, but B. ceiba stem bark extract at 100 µg/mL caused 16.8±1.9% hemolysis, and Triton X-100 (0.1%; positive control) caused 99.1±0.4% hemolysis. B. ceiba’s aqueous extract contained flavonoid and phenolic components, which enhanced Bc-AgNPs’ antioxidant capacity. The relative IC50 values were 28.03±0.98 µg/mL and 33.7±0.38 µg/mL. When compared to a reference medication, Bc-AgNPs demonstrated a moderate antiinflammatory effect, with IC50 values of 42.26±0.74 µg/mL for BSA and 50.93±1.07 µg/mL for egg albumin assay. According to the study, bio/hemocompatible Bc-AgNPs may be a viable treatment choice for antiinflammatory and antioxidant treatments.
Keywords: Antihemolytic activity; Antioxidant activity; Silver nanoparticles; Antiinflammatory activity; Biosynthesis